Patients under Psychiatric Medication Undergoing Cardiac Surgery Have a Higher Risk for Adverse Events - Brunner, Sandra; Diez, Claudius; Flörchinger, Bernhard; Kolat, Philipp; Schmid, Christof; Camboni, Daniele (The Thoracic and Cardiovascular Surgeon, 2016)
Objective The percentage of patients undergoing cardiac surgery under some sort of psychiatric medication (PM) is not negligible. Thus, this study aimed to evaluate a possible impact of preoperative PM on the outcome after cardiac surgery.Methods A matched case–control study was conducted by including all patients who underwent myocardial revascularization and/or surgical valve operation in our institution from December 2008 till February 2011 by chart review and institutional quality assurance database (QS) analysis. Results Out of 1,949 patients included, 184 patients (9%) were identified with PM medication (group A). A control group matched for logistic EuroSCORE II, ejection fraction and age was generated (group C). Patients with PM were in mean significantly longer on the intensive care unit (A: 4.94 days; 95% confidence interval (CI), 3.9–5.9 days vs. C: 3.24 days; CI, 2.84–3.64 days; p = 0.003), had longer mechanical ventilation times (A: 36.70 hours; CI, 19.81–53.59 hours vs. C: 20.14 hours; CI, 14.61–25.68 hours; p = 0.258), and significantly more episodes of respiratory insufficiencies (A: 31 episodes [17%] vs. C: 17 episodes [9%]; p = 0.002). Regression analysis revealed preoperative PM as a significant risk factor for respiratory insufficiency (odds ratio: 1.99, CI: 1.0–3.74; p = 0.04). Chest tube drainage (A: 690 mL, CI: 571–808 mL vs. C: 690 mL; CI: 496–884 mL, p = 0.53) and the total amount of red blood cell transfusion units were similar (A: 1.69 units; CI: 1.21–2.18 units vs. C: 1.50 units; CI: 1.04–1.96 units; p = 0.37). Sternal dehiscence requiring sternal refixation was significantly more frequent in A (12 patients [7%] vs. C: 2 patients [1%]; odds ratio: 6.3, CI: 1.4–28.7; p = 0.01). The 30-day mortality was similar in both groups (A: 6 patients [3%] vs. C: 4 patients [2%]; odds ratio: 1.5; CI: 0.4–5.4; p = 0.5); however, the 100-day mortality was near significantly higher in group A (A: 14 patients (8%) vs. C: 6 patients (3%); odds ratio: 2.4, CI: 0.9–6.5, p = 0.057).Conclusion Patients with preoperative PM developed complications more frequently compared with a matched control group. The underlying multifactorial mechanisms remain unclear. Patients under PM need to be identified and particular care including optimal pre- and postoperative psychiatric assistance is recommended.
Keywords: psychiatric medication; antidepressant medication; coronary artery bypass graft; aortic valve replacement; outcome